ABCC8 and KCNJ11 molecular spectrum of 109 patients with diazoxide-unresponsive congenital hyperinsulinism. Issue 11 (3rd August 2010) - Bellanné-Chantelot, C; Saint-Martin, C; Ribeiro, M-J; Vaury, C; Verkarre, V; Arnoux, J-B; Valayannopoulos, V; Gobrecht, S; Sempoux, C; Rahier, J; Fournet, J-C; Jaubert, F; et al.
Abstract : Background: Congenital hyperinsulinism (CHI) is characterised by an over secretion of insulin by the pancreatic β-cells. This condition is mostly caused by mutations in ABCC8 or KCNJ11 genes encoding the SUR1 and KIR6.2 subunits of the ATP-sensitive potassium (KATP ) channel. CHI patients are classified according to their responsiveness to diazoxide and to their histopathological diagnosis (either focal, diffuse or atypical forms). Here, we raise the benefits/limits of the genetic diagnosis in the clinical management of CHI patients. Methods: ABCC8 / KCNJ11 mutational spectrum was established in 109 diazoxide-unresponsive CHI patients for whom an appropriate clinical management is essential to prevent brain damage. Relationships between genotype and radiopathological diagnosis were analysed. Results: ABCC8 or KCNJ11 defects were found in 82% of the CHI cases. All patients with a focal form were associated with a single KATP channel molecular event. In contrast, patients with diffuse forms were genetically more heterogeneous: 47% were associated with recessively inherited mutations, 34% carried a single heterozygous mutation and 19% had no mutation. There appeared to be a predominance of paternally inherited mutations in patients diagnosed with a diffuse form and carrying a sole KATP channel mutation. Conclusions: The identification of recessively inherited mutations related to severe and diffuse forms of CHI provides an informative genetic diagnosis and allows prenatal diagnosis. In contrast, in patients carrying a single KATP channel mutation, genetic analysis should be confronted with the PET imaging to categorise patients as focal or diffuse forms in order to get the appropriate therapeutic management.